Word of Editor-in-Chief - Antonijević, Dragana (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2006)
Dear colleagues, In front of you is the first issue of the new series of Issues in Ethnology and Anthropology, journal of the Department of Ethnology and Anthropology, Faculty of Philosophy, University of Belgrade. The profile of the journal is comprehensible and straightforward: we are open to all contemporary and innovative tendencies, theoretically and methodologically founded scientific papers in the field of ethnology, anthropology, folkloristic and other contiguous disciplines.... We welcome your interest and contribution in Issues in Ethnology and Anthropology, and will consider it our goal – achievement for you to cite our publication in your papers, for it is our intention to become a reference publication, both on the domestic and international scientific terrain...